‘Unhappy News’: Process, Rhetoric, and Context in the Making of the Happiness Problem - Ashley Frawley (Sociological Research Online, 2018)
This article examines the emergence and spread of happiness as a social problem, drawing on a study of UK national newspapers. It draws on insights from social problems constructionism and related social movement theory to analyse the rise of the phenomenon in terms of the processual, rhetorical, and contextual factors involved in its construction, transmission and institutionalisation. Issue ownership, flexible syntax, experiential commensurability, empirical credibility and narrative fidelity are argued to have contributed to the discursive spread of happiness as a social problem in this public arena. A cultural context hospitable to claims about social issues constructed in highly individualised and personalised terms is argued to have contributed to the issue's widespread embrace.